A kind of phosphorus-free corrosion and scale inhibitor and preparation method thereof
Through the preparation method of phosphorus-free corrosion-resisting scale inhibitor, polymer cross-linking method and modified nanotitanium dioxide form a deposited film, which solves the water pollution caused by phosphorus content in existing scale inhibitors and the use of high temperature and high alkali conditions under high temperature and high alkaline conditions The problem limits can achieve efficient and economical anti-scaling effect and antibacterial properties.
Patent Information
- Application Number
- CN202411453638.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-10-17
AI Technical Summary
The phosphorus-containing substances in existing scale inhibitors are prone to eutrophication of water, and are limited in use under high temperature, high alkali and high hardness conditions, and the utilization rate of liquid scale inhibitors is low.
The preparation method of phosphorus-free corrosion-resisting agent is adopted to form polymer aggregates with a network structure through polymer cross-linking method, and combined with modified nanotitanium dioxide to form a deposited film to prevent scale formation, and at the same time, sulfuric acid groups are introduced to Slows the formation of insoluble inorganic salts.
It achieves effective scale inhibition effect under high temperature, high alkali and high hardness conditions, slows down the speed of microcrystalline scale formation, improves the utilization rate of scale inhibitors, and has excellent antibacterial properties.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of scale inhibitors, in particular to a phosphorus-free corrosion and scale inhibitor and a preparation method thereof. Background Art
[0002] In order to solve the water resource crisis, people have continuously improved technology and developed technologies such as seawater desalination and water recycling. Water injection for oil recovery is a common technology used in many oil fields. In order to avoid environmental pollution caused by the discharge of oil field produced water, many oil fields inject the treated produced water back into the formation as injection water. However, the mineralization degree of produced water is relatively high and contains many different types of ion components. During the process of oil field produced water reinjection, the temperature and pressure in the water body will change, resulting in inorganic mineral scale (referred to as scale) on the surface of hot and cold water systems, pipelines, heat exchangers and other equipment. The scale will reduce the efficiency of pipelines and equipment and cause waste of water resources. At the same time, the formation of scale will shorten the service life of equipment, accelerate metal corrosion, increase maintenance costs, and pose a serious threat to the safe operation of equipment, resulting in huge economic losses.
[0003] Faced with the increasingly serious scaling problem, the scale inhibition methods used in industry are mainly divided into three categories: chemical scale inhibition, physical scale inhibition and process scale inhibition. Chemical scale inhibition refers to the use of chemical methods such as adding scale inhibitors to prevent scale from forming during operation; physical scale inhibition mainly refers to the removal of scale by physical action such as mechanical means; process scale inhibition is to prevent scale formation by changing process conditions or parameters. Among them, chemical scale inhibition is simple and fast to operate, low in price and has a significant scale inhibition effect, so it has attracted much attention. Adding scale inhibitors is the most common and effective chemical scale inhibition method to prevent scale formation. Because organic phosphonate scale inhibitors have good scale inhibition properties, they have become the most widely used scale inhibitors at home and abroad. However, the discharge of these phosphorus-containing substances will pollute the water environment, easily produce bacteria and algae, and make the water body eutrophic. In addition, organic phosphonates are easy to decompose, which limits their use under high temperature, high alkali and high hardness conditions. Most of the scale inhibitors currently used are liquid scale inhibitors, which are easily washed away with water, leading to problems with the utilization rate of scale inhibitors. Summary of the invention
[0004] The purpose of the present invention is to provide a phosphorus-free corrosion and scale inhibitor and a preparation method thereof, so as to solve the problems existing in the prior art.
[0005] In order to solve the above technical problems, the present invention provides the following technical solution: a method for preparing a phosphorus-free corrosion and scale inhibitor, comprising the following preparation steps:
[0006] Step (1): dissolving 6 to 14 parts of titanium tetraisopropoxide in 54 to 126 parts of ethanol, adding 1 to 3 parts of deionized water, stirring at 180 rpm for 20 to 40 minutes, ultrasonicating at 35 to 45° C. and 40 to 50 kHz for 15 to 25 minutes, placing in a drying oven at 90 to 110° C. and drying for 16 to 32 hours, then placing in a muffle furnace and heating to 350 to 450° C. at a certain heating rate under nitrogen protection, spraying 1 to 3 parts of zinc sulfate aqueous solution, calcining for 2 hours or 3 hours, and grinding into a powder with a particle size of 5 nm to obtain modified nano titanium dioxide;
[0007] Step (2): placing 5 to 15 parts of a polyhexamethylene biguanide hydrochloride aqueous solution in a container, adding dropwise 2 to 6 parts of a poly(potassium) sulfate aqueous solution, and stirring at 30 to 40° C. and 160 rpm for 1 to 3 hours to obtain an aggregate suspension;
[0008] Step (3): Disperse 4 to 10 parts of modified nano titanium dioxide in 36 to 108 parts of deionized water, add 27 to 69 parts of aggregate suspension, stir at 170 rpm for 20 to 30 minutes, centrifuge for 10 to 20 minutes, wash the solid with deionized water for 3 times, and dry at 50 to 70° C. for 8 to 16 hours to obtain a phosphorus-free corrosion and scale inhibitor.
[0009] Furthermore, the preparation method of the zinc sulfate aqueous solution in step (1) is: dissolving 0.06 parts of zinc sulfate in 18 parts of ethanol, and adjusting the pH of the solution to 2-3 with an acetic acid aqueous solution to obtain the zinc sulfate aqueous solution.
[0010] Furthermore, the concentration of the acetic acid aqueous solution is 1 mol / L.
[0011] Furthermore, the heating to 350-450° C. in step (1) is performed at a heating rate of 10° C. / min.
[0012] Furthermore, the concentration of the polyhexamethylene biguanide hydrochloride aqueous solution in step (2) is 1 mg / mL.
[0013] Furthermore, the concentration of the potassium polyvinyl sulfate aqueous solution in step (2) is 12 mg / mL.
[0014] Furthermore, in step (2), the potassium polyvinyl sulfate aqueous solution is adjusted to pH 3 by using a sodium hydroxide aqueous solution having a concentration of 3 mol / L.
[0015] Furthermore, the dripping rate in step (2) is 2 mL / min.
[0016] Furthermore, the centrifugal speed in step (3) is 3000-5000 r / min.
[0017] A phosphorus-free corrosion and scale inhibitor is prepared by the above-mentioned preparation method.
[0018] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0019] The invention firstly utilizes a polymer cross-linking method to cross-link polyethylene potassium sulfate and polyhexamethylene biguanide hydrochloride to form a polymer aggregate with a network structure, which can form a deposition film on the metal surface, reduce the collision and coagulation probability between microcrystalline particles, slow down the scaling speed of microcrystalline, and preliminarily achieve the scale inhibition effect; the sulfate group introduced by the polyethylene potassium sulfate forms a coordination bond with the metal cation in the solution, improves the solubility of the cation in the solution, slows down and inhibits the formation of insoluble inorganic salts, and further achieves the scale inhibition effect; the guanidine structure in the polyhexamethylene biguanide hydrochloride can specifically interact with the bacterial ribosome RNA part, block the normal chain reaction required for protein synthesis, and can interact with the ring structure of bacterial DNA, block its replication and repair process, and cause the breakage and damage of the bacterial DNA chain, thereby achieving the antibacterial effect; finally, through the charge attraction effect, the modified nano titanium dioxide is enriched on the surface of the polymer aggregate, occupies the active site of microcrystalline growth, causes the crystal surface to be distorted, causes lattice distortion, and inhibits the normal growth of the crystal, thereby achieving the scale inhibition effect.
[0020] Among them, modified nano titanium dioxide is prepared by gelling titanium tetraisopropoxide and then high-temperature atomizing spraying zinc sulfate solution; metal zinc ions are doped into vacant positions of titanium dioxide by high-temperature atomizing spraying to obtain modified nano titanium dioxide. The modified titanium dioxide has stronger adsorption force, and its light absorption capacity in the visible light region is also significantly improved, which can promote the effective separation of carriers to achieve the effect of enhancing the antibacterial properties; at the same time, doping with zinc ions enables it to quickly form a deposited film on the surface, cooperate with polymer aggregates, accelerate its film formation, and improve the durability of the film, thereby achieving excellent corrosion inhibition effect. DETAILED DESCRIPTION
[0021] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0022] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the various index testing methods of the phosphorus-free corrosion and scale inhibitor prepared in the following examples are as follows:
[0023] Scale inhibition rate: Take the same mass of the example and the comparative example, use deionized water to prepare the scale inhibitor with a concentration of 40 mg / L, add Ca 2+ Mass concentration 240mg / L, HCO 3 - The mass concentration was 732 mg / L in a constant temperature water bath at 80 ° C, kept warm for 10 h, cooled, filtered with a 0.22 μm microporous filter, and the Ca was determined by the EDTA method. 2+ concentration and perform a blank test at the same time.
[0024] The scale inhibition rate η is calculated according to the formula η=C 1 -C 0 / C 2 -C 0 calculate
[0025] Among them, C 1 : Calcium ion concentration after adding scale inhibitor, mg / L; C 0 : Calcium ion concentration mg / L after blank test solution without scale inhibitor; C 2 : Calcium ion concentration in the test solution prepared before the test, mg / L.
[0026] Carbon steel corrosion rate and brass corrosion rate: Take the same mass of the embodiment and the comparative example, and test them according to GB / T 18175. The test conditions are temperature 45±1°C, test piece material A3 carbon steel, rotation speed 80 r / min, no pre-filming, and test time 72h.
[0027] Inhibition diameter: Take the same mass of the embodiment and the comparative example, prepare a solution with a concentration of 80μg / mL, and use the Oxford cup method to test the size of the inhibition zone of Escherichia coli on the agar medium. Place the Oxford cups on the agar medium inoculated with Escherichia coli, add the above-mentioned scale inhibitor solutions of different concentrations, and culture at a constant temperature of 37°C for 50 days, and measure the diameter of the inhibition zone of each sample with a ruler.
[0028] Example 1: (1) 0.06 parts of zinc sulfate were dissolved in 18 parts of water, and the pH of the solution was adjusted to 2 with 1 mol / L acetic acid aqueous solution to prepare a zinc sulfate aqueous solution;
[0029] (2) 6 parts of titanium tetraisopropoxide were dissolved in 54 parts of ethanol, 1 part of deionized water was added, stirred at 180 rpm for 20 min, ultrasonicated at 35° C. and 40 kHz for 15 min, dried in a drying oven at 90° C. for 16 h, then placed in a muffle furnace and heated to 350° C. at 10° C. / min under nitrogen protection, 1 part of zinc sulfate aqueous solution was sprayed into it by atomization, calcined for 2 h, and ground into a powder with a particle size of 5 nm to obtain modified nano titanium dioxide;
[0030] (3) placing 5 parts of a 1 mg / mL aqueous solution of polyhexamethylene biguanide hydrochloride in a container, adding 2 parts of a 12 mg / mL aqueous solution of polyvinyl potassium sulfate adjusted to pH 3 by a 3 mol / L aqueous solution of sodium hydroxide at a rate of 2 mL / min, and stirring at 30° C. and 160 rpm for 1 h to prepare an aggregate suspension;
[0031] (4) Disperse 4 parts of modified nano-titanium dioxide in 36 parts of deionized water, add 27 parts of aggregate suspension, stir at 170 rpm for 20 min, centrifuge at 3000 r / min for 10 min, wash the solid with deionized water for 3 times, and dry at 50°C for 8 h to obtain a phosphorus-free corrosion and scale inhibitor.
[0032] Example 2: (1) 0.06 parts of zinc sulfate were dissolved in 18 parts of water, and the pH of the solution was adjusted to 2.5 with an aqueous solution of acetic acid having a concentration of 1 mol / L to prepare an aqueous solution of zinc sulfate;
[0033] (2) 10 parts of titanium tetraisopropoxide were dissolved in 90 parts of ethanol, 2 parts of deionized water were added, stirred at 180 rpm for 30 min, ultrasonicated at 40° C. and 45 kHz for 20 min, dried in a drying oven at 100° C. for 24 h, then placed in a muffle furnace and heated to 400° C. at 10° C. / min under nitrogen protection, 2 parts of zinc sulfate aqueous solution were sprayed into the mixture by atomization, calcined for 3 h, and ground into a powder with a particle size of 5 nm to obtain modified nano titanium dioxide;
[0034] (3) 10 parts of a 1 mg / mL aqueous solution of polyhexamethylene biguanide hydrochloride were placed in a container, and 4 parts of a 12 mg / mL aqueous solution of polyvinyl potassium sulfate was added dropwise at a rate of 2 mL / min, the pH of the solution being adjusted to 3 by a 3 mol / L aqueous solution of sodium hydroxide, and the solution was stirred at 35° C. and 160 rpm for 2 h to prepare an aggregate suspension;
[0035] (4) Disperse 7 parts of modified nano-titanium dioxide in 72 parts of deionized water, add 48 parts of aggregate suspension, stir at 170 rpm for 25 min, centrifuge at 4000 r / min for 15 min, wash the solid with deionized water for 3 times, and dry at 60°C for 12 h to obtain a phosphorus-free corrosion and scale inhibitor.
[0036] Example 3: (1) 0.06 parts of zinc sulfate were dissolved in 18 parts of water, and the pH of the solution was adjusted to 3 with 1 mol / L acetic acid aqueous solution to prepare a zinc sulfate aqueous solution;
[0037] (2) 14 parts of titanium tetraisopropoxide were dissolved in 126 parts of ethanol, 3 parts of deionized water were added, and the mixture was stirred at 180 rpm for 40 min, ultrasonicated at 45° C. and 50 kHz for 25 min, and dried in a drying oven at 110° C. for 32 h. The mixture was then placed in a muffle furnace and heated to 450° C. at a rate of 10° C. / min under nitrogen protection, and 3 parts of an aqueous zinc sulfate solution were sprayed into the mixture by atomization. The mixture was calcined for 2 h, and ground into a powder with a particle size of 5 nm to obtain modified nano-titanium dioxide;
[0038] (3) placing 15 parts of a 1 mg / mL aqueous solution of polyhexamethylene biguanide hydrochloride in a container, adding 6 parts of a 12 mg / mL aqueous solution of polyvinyl potassium sulfate adjusted to pH 3 by a 3 mol / L aqueous solution of sodium hydroxide at a rate of 2 mL / min, and stirring at 40° C. and 160 rpm for 3 h to obtain an aggregate suspension;
[0039] (4) Disperse 10 parts of modified nano-titanium dioxide in 108 parts of deionized water, add 69 parts of aggregate suspension, stir at 170 rpm for 30 min, centrifuge at 5000 r / min for 20 min, wash the solid with deionized water for 3 times, and dry at 70°C for 16 h to obtain a phosphorus-free corrosion and scale inhibitor.
[0040] Comparative Example 1: The difference between Comparative Example 1 and Example 2 is that step (3) is omitted. The method of step (4) is as follows: 7 parts of modified nano titanium dioxide are dispersed in 72 parts of deionized water, 48 parts of a 1 mg / mL polyhexamethylene biguanide hydrochloride aqueous solution are added, stirred at 170 rpm for 25 min, centrifuged at 4000 r / min for 15 min in a centrifuge, the solid is washed with deionized water for 3 times, and dried at 60° C. for 12 h to obtain a phosphorus-free corrosion and scale inhibitor. The remaining steps are the same as those of Example 2.
[0041] Comparative Example 2: The difference between Comparative Example 2 and Example 2 is that step (3) is omitted. Step (4) is as follows: 7 parts of modified nano titanium dioxide are dispersed in 72 parts of deionized water, 48 parts of a 12 mg / mL aqueous solution of polyvinyl potassium sulfate adjusted to pH 3 by a 3 mol / L sodium hydroxide aqueous solution are added, the mixture is stirred at 170 rpm for 25 min, centrifuged at 4000 r / min in a centrifuge for 15 min, the solid is washed three times with deionized water, and dried at 60° C. for 12 h to obtain a phosphorus-free corrosion and scale inhibitor. The remaining steps are the same as those in Example 2.
[0042] Comparative Example 3: The difference between Comparative Example 3 and Example 2 lies in the difference between step (2) and step (4). The method of step (2) is as follows: stirring the zinc sulfate aqueous solution at 180 rpm for 30 min, ultrasonicating at 40°C and 45 kHz for 20 min, placing it in a drying oven at 100°C for 24 h, then placing it in a muffle furnace and heating it to 400°C at 10°C / min for calcining for 1.5 h, grinding it into a powder with a particle size of 5 nm, and obtaining modified nano zinc oxide; the method of step (4) is as follows: dispersing 7 parts of modified nano zinc oxide in 72 parts of deionized water, adding 48 parts of aggregate suspension, stirring at 170 rpm for 25 min, placing it in a centrifuge at 4000 r / min for 15 min, washing the solid with deionized water three times, and drying it at 60°C for 12 h, and obtaining a phosphorus-free corrosion and scale inhibitor. The remaining steps are the same as those of Example 2.
[0043] Comparative Example 4: The difference between Comparative Example 4 and Example 2 is that there is no step (1), and the method of step (2) is: 10 parts of titanium tetraisopropoxide are dissolved in 90 parts of ethanol, 2 parts of deionized water are added, stirred at 180 rpm for 30 minutes, ultrasonicated at 40°C and 45kHz for 20 minutes, placed in a drying oven at 100°C for 24 hours, then placed in a muffle furnace under nitrogen protection and heated to 400°C at 10°C / min for calcination for 1.5 hours, ground into a powder with a particle size of 5 nm, and prepared modified nano titanium dioxide. The remaining steps are the same as those in Example 2.
[0044] Comparative Example 5: The difference between Comparative Example 5 and Example 2 is the difference in step (2). The method of step (2) is as follows: 10 parts of titanium tetraisopropoxide are dissolved in 90 parts of water, 2 parts of zinc sulfate aqueous solution are added, and the mixture is stirred at 180 rpm for 10 min, then transferred into a reaction kettle, reacted at 220° C. and 200 rpm for 12 h, cooled naturally to 25° C., washed with deionized water 3 times, dried at 65° C. for 10 h, and ground into a powder with a particle size of 5 nm to obtain modified nano titanium dioxide. The remaining steps are the same as those in Example 2.
[0045] Comparative Example 6: The difference between Comparative Example 6 and Example 2 is that steps (1), (2) and (4) are omitted. The remaining steps are the same as those in Example 2.
[0046] Effect example
[0047] Table 1 below shows the performance analysis results of the phosphorus-free corrosion and scale inhibitors of Examples 1 to 3 of the present invention and Comparative Examples 1 to 6.
[0048] Table 1
[0049]
[0050] From the comparison of the experimental data of Examples 1, 2, and 3 with those of Comparative Example 1, it can be found that the sulfate groups introduced by potassium polyvinyl sulfate form coordination bonds with metal cations in the solution, thereby increasing the solubility of cations in the solution, slowing down and inhibiting the formation of insoluble inorganic salts, and thus achieving a scale inhibition effect; from the comparison of the experimental data of Examples 1, 2, and 3 with those of Comparative Example 2, it can be found that the polymer aggregates with a network structure formed by a polymer cross-linking method can form a deposition film on the metal surface, reduce the probability of collision and agglomeration between microcrystalline particles, slow down the speed of microcrystalline scaling, and preliminarily achieve a scale inhibition effect; from the comparison of the experimental data of Examples 1, 2, and 3 with those of Comparative Example 3, it can be found that titanium dioxide has a strong adsorption force, can promote the effective separation of carriers, and achieve the effect of enhancing antibacterial properties; from the comparison of the experimental data of Examples 1, 2, and 3 with those of Comparative Example 4, it can be found that doping with zinc ions makes it It can quickly form a deposited film on the surface, cooperate with polymer aggregates to accelerate its film formation, and improve the durability of the film, thereby achieving excellent corrosion inhibition effect; from the comparison of the experimental data of Examples 1, 2, and 3 with Comparative Example 5, it can be found that the modified nano-titanium dioxide obtained by first making titanium tetraisopropoxide into a gel and then spraying a zinc sulfate aqueous solution at high temperature has a stronger adsorption force, and the metal zinc ions are doped into the vacant positions of titanium dioxide, and the light absorption capacity in the visible light region is also significantly improved, which can promote the effective separation of carriers and achieve the effect of enhancing the antibacterial performance; from the comparison of the experimental data of Examples 1, 2, and 3 with Comparative Example 6, it can be found that through the charge attraction, the modified nano-titanium dioxide is enriched on the surface of the polymer aggregate, occupying the active sites of microcrystal growth, causing the crystal surface to be distorted, causing lattice distortion, inhibiting the normal growth of the crystal, and achieving the scale inhibition effect.
[0051] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.
Claims
1. A method for preparing a phosphorus-free corrosion and scale inhibitor, characterized in that: The method comprises the following preparation steps: Step (1): dissolving 6 to 14 parts of titanium tetraisopropoxide in 54 to 126 parts of ethanol, adding 1 to 3 parts of deionized water, stirring at 180 rpm for 20 to 40 minutes, ultrasonicating at 35 to 45° C. and 40 to 50 kHz for 15 to 25 minutes, placing in a drying oven at 90 to 110° C. and drying for 16 to 32 hours, then placing in a muffle furnace and heating to 350 to 450° C. at a certain heating rate under nitrogen protection, spraying 1 to 3 parts of zinc sulfate aqueous solution, calcining for 2 hours or 3 hours, and grinding into a powder with a particle size of 5 nm to obtain modified nano titanium dioxide; Step (2): placing 5 to 15 parts of a polyhexamethylene biguanide hydrochloride aqueous solution in a container, adding dropwise 2 to 6 parts of a poly(potassium) sulfate aqueous solution, and stirring at 30 to 40° C. and 160 rpm for 1 to 3 hours to obtain an aggregate suspension; Step (3): Disperse 4 to 10 parts of modified nano titanium dioxide in 36 to 108 parts of deionized water, add 27 to 69 parts of aggregate suspension, stir at 170 rpm for 20 to 30 minutes, centrifuge for 10 to 20 minutes, wash the solid with deionized water for 3 times, and dry at 50 to 70° C. for 8 to 16 hours to obtain a phosphorus-free corrosion and scale inhibitor.
2. The method for preparing a phosphorus-free corrosion and scale inhibitor according to claim 1, characterized in that: The preparation method of the zinc sulfate aqueous solution in step (1) is as follows: 0.06 parts of zinc sulfate are dissolved in 18 parts of water, and the pH of the solution is adjusted to 2-3 with an acetic acid aqueous solution to obtain the zinc sulfate aqueous solution.
3. The method for preparing a phosphorus-free corrosion and scale inhibitor according to claim 2, characterized in that: The concentration of the acetic acid aqueous solution is 1 mol / L.
4. The method for preparing a phosphorus-free corrosion and scale inhibitor according to claim 1, characterized in that: The heating to 350-450°C in step (1) is carried out at a heating rate of 10°C / min.
5. The method for preparing a phosphorus-free corrosion and scale inhibitor according to claim 1, characterized in that: The concentration of the polyhexamethylene biguanide hydrochloride aqueous solution in step (2) is 1 mg / mL.
6. The method for preparing a phosphorus-free corrosion and scale inhibitor according to claim 1, characterized in that: The concentration of the potassium polysulfate aqueous solution in step (2) is 12 mg / mL.
7. The method for preparing a phosphorus-free corrosion and scale inhibitor according to claim 1, characterized in that: In step (2), the potassium polyvinyl sulfate aqueous solution is adjusted to pH 3 by using a 3 mol / L sodium hydroxide aqueous solution.
8. The method for preparing a phosphorus-free corrosion and scale inhibitor according to claim 1, characterized in that: The rate of the dropping in step (2) is 2 mL / min, and the speed of the centrifugation in step (3) is 3000-5000 r / min.
9. A phosphorus-free corrosion and scale inhibitor, characterized in that: Prepared according to any one of claims 1 to 8.
Citation Information
Patent Citations
Surface modification method for titanium dioxide mingled with zinc
CN104923207A
Environment-friendly nano-fluid scale inhibitor as well as preparation method and application thereof
CN114656044A
Preparation method of bio-based scale inhibitor
CN118684360A
Durable antibacterial polymer complexes
KR1020000059741A